2013
DOI: 10.1002/eji.201242676
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1 on activated NK cells inhibits NKG2D‐mediated cytolytic function and signaling

Abstract: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is expressed on activated natural killer (NK) cells wherein it inhibits lysis of CEACAM1-bearing tumor cell lines. The mechanism for this is unknown. Here we show that interleukin-2-induced expression of CEACAM1 on both mouse and primary human NK cells impairs the ability of NKG2D to stimulate cytolysis of CEACAM1-bearing cells. This process requires the expression of CEACAM1 on the NK cell and on the tumor cells, which is consistent with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…Mutagenesis analysis demonstrated that key residues (R43 Q44) on the GFCC'C" surface were critical for CEACAM1-L's inhibitory function on NK cells [32]. Upon trans dimerization and clustering on the NK cell surface, CEACAM1 associates with the activating NKG2D receptor resulting in SHP-1-mediated dephosphorylation of the guanine nucleotide exchange factor Vav1 and consequential disruption of cytolysis [95].…”
Section: Ceacam1 Inhibits Natural Killer Cell-mediated Cytotoxicity-nmentioning
confidence: 99%
“…Mutagenesis analysis demonstrated that key residues (R43 Q44) on the GFCC'C" surface were critical for CEACAM1-L's inhibitory function on NK cells [32]. Upon trans dimerization and clustering on the NK cell surface, CEACAM1 associates with the activating NKG2D receptor resulting in SHP-1-mediated dephosphorylation of the guanine nucleotide exchange factor Vav1 and consequential disruption of cytolysis [95].…”
Section: Ceacam1 Inhibits Natural Killer Cell-mediated Cytotoxicity-nmentioning
confidence: 99%
“…On the surface membrane, CEACAM1 acts as a co-inhibitory receptor of the T cell receptor (TCR)/ CD3 complex through homophilic interactions, especially if the antigen-presenting cell expresses CEACAM1, such as B cell, dentritic cell and macrophage. This results in inhibiting cytokine production (mostly IFNγ-dominant Th1) and cytotoxicity in NK cells via a class I MHC-independent inhibitory mechanism [226][227][228].…”
Section: Loss Of Ceacam1 Causes Insulin Resistance Visceral Obesitymentioning
confidence: 99%
“…In addition, many IgSF proteins have incorporated distinct functionalities, illustrated by the presence of a mucin-like domain in the TIM proteins and distinct cytoplasmic domains across the family members shown. TM transmembrane, Tyr (P) tyrosine phosphorylation activity, including signaling and the induction of cytotoxic activity (Hosomi et al 2013 ). This activity appears to be due to the regulation of NKG2D cell surface expression by CEACAM1 signaling (Chen et al 2011 ).…”
Section: Ceacam1mentioning
confidence: 99%